Public knowledge and awareness of appropriate antibiotic use in Indonesia: A review of regional patterns and misconceptions - Oktariza, Yasinda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
Inappropriate use of antibiotics is one of the major contributors to the rising incidence of antimicrobial resistance. Public knowledge plays a critical role in shaping appropriate antibiotic use behaviors. This review aims to assess the level of knowledge and awareness regarding antibiotics among communities across selected regions in Indonesia and identified persistent misconceptions. A literature search was conducted using PubMed and Google Scholar databases for studies published between 2020-2025. Cross-sectional studies examining public antibiotic knowledge in Indonesian populations were included. Quality assessment was performed using the CASP Checklist for cross-sectional studies. A total of ten articles met the eligibility criteria, each representing different provinces in Indonesia. All studies employed questionnaires as their primary data collection instruments. The review findings indicate that public knowledge and awareness of antibiotics remain moderate. Persistent misconceptions included beliefs that antibiotics treat viral infections, cold and cough symptoms, and fever. Non-prescription antibiotic procurement rates ranged from 40-52%, while 50-74% discontinued treatment when feeling better. To address these issues, targeted educational interventions are necessary, involving both active and passive dissemination strategies and engagement with healthcare professionals. Increasing public understanding of antibiotic use is expected to contribute to the reduction of antimicrobial resistance in Indonesia.